The interaction of chemical reaction and thermal stress in the processing and applications of ceramics - Thiart, Jacob Johannes (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D. (Chem. Eng.)) -- University of Stellenbosch, 1991.